Assessment of Fetal Kidney Growth and Birth Weight in an Indigenous Australian Cohort - Diehm, Christopher J.; Lumbers, Eugenie R.; Weatherall, Loretta; Keogh, Lyniece; Eades, Sandra; Brown, Alex; Smith, Roger; Johnson, Vanessa; Pringle, Kirsty G.; Rae, Kym M. (Frontiers in Physiology, 2018)
Introduction Indigenous Australians experience higher rates of renal disease and hypertension than non-Indigenous Australians. Low birth weight is recognised as a contributing factor in chronic disease and has been shown to increase the risk of renal failure in adulthood. A smaller kidney volume with fewer nephrons places an individual at risk of hypertension and renal failure. Indigenous Australians have fewer nephrons than non-Indigenous Australians. In this study, intrauterine fetal and kidney growth were evaluated in 174 Indigenous Australian babies throughout gestation in order to record and evaluate fetal growth and kidney size, within a population that is at high risk for chronic illness. Methods Pregnant women that identified as Indigenous, or non-Indigenous women that were pregnant with a partner who identified as an Indigenous Australian were eligible to participate. Maternal history, smoking status, blood and urine samples and fetal ultrasounds were collected throughout pregnancy. Fetal kidney measurements were collected using ultrasound. Statistical analysis was performed using the Stata 14.1 software package. Results 15.2% of babies were born prematurely. 44% of the mothers reported smoking in pregnancy. The median birth weight of this cohort was 3240 grams. Male fetuses had higher kidney to body weight ratios than female fetuses (P=0.02). The birth weights of term neonates whose mothers smoked during pregnancy were lower (327 grams, P<0.001) than the birth weights of term babies from non-smoking mothers. The kidney volumes of babies whose mothers smoked were also smaller (P=0.02), but were in proportion to body weight. Conclusion In this cohort of Indigenous women smoking was associated with both increased number of preterm births and with a reduction in birth weights, even of term infants. Since kidney volume is a surrogate measure of nephron number and nephrogenesis is complete at birth, babies whose mothers smoked during pregnancy must have fewer nephrons than those from non-smoking mothers. Previous studies have shown that glomerular filtration rate is not related to birth weight, thus infants with smaller kidney volumes are hyperfiltering from birth and therefore are likely to be more susceptible to early onset renal disease in later life.